Association between oxidative balance score and cardiovascular diseases: mediating analysis of methylmalonic acid based on the NHANES database - Yang, Xinyu; Zhang, Zisang; Ye, Fei; Liu, Pengfei; Peng, Bo; Wang, Teng (Frontiers in Nutrition, 2024)
Aim: To explore the association between oxidative balance score (OBS) and cardiovascular diseases (CVD) in patients with hypertension, and further clarify the mediating role of methylmalonic acid (MMA) in the relationship between OBS and CVD risk.We included 4137 participants with hypertension from the 2011-2014 National Health and Nutrition Examination Survey cohort. The study endpoint was the incidence of CVD in patients with hypertension. OBS was calculated based on 16 dietary and 4 lifestyle components. Weighted multivariable logistic regression models were adopted to assess the associations between OBS and CVD risk, OBS and MMA levels, and MMA levels and CVD risk. Odds ratios (OR) and 95% confidence interval (CI) were estimated. We used distribution-of-product method to test for mediation effect, with a presence of mediation indicated by 95% CI that does not include 0 for the distribution-of-product method and 95% CI that does not include 1 for the indirect effect.Results: Totally 812 developed CVD. In weighted multivariable logistic regression models, lower OBS category (OBS<15.72) was associated with increased odds of CVD (OR=1.53, 95%CI: 1.17-2.01) and MMA levels (OR=1.32, 95%CI: 1.06-1.65), respectively, compared with higher OBS category as reference. A positive relationship between higher MMA levels (≥154.90 nmol/L) and CVD risk was observed (OR=1.34, 95%CI: 1.07-1.68). Importantly, according to the distribution-of-product test, a potential mediating effect of MMA on the relationship between OBS and CVD was Association between OBS and CVDs 3 found (OR=1.08, 95%CI: 1.01-1.19), with a 95% CI for distribution-of-product of 0.08 (95% CI: 0.01-0.17). The mediated proportion was 17.8%. Subgroup analysis revealed a mediating effect of MMA in individuals with dyslipidemia, with a mediated proportion of 14.9%.MMA plays a critical mediating role in the pathway between OBS and CVD risk.